Initiation and processing of two kappa immunoglobulin germ line transcripts in mouse B cells. - Martin, D J (1990)
The splicing patterns and sequences of two processed kappa immunoglobulin germ line mRNAs are presented. A 1.1-kilobase (kb) mRNA appeared to be derived from splicing of the previously characterized 8.4-kb germ line transcript, while a 0.8-kb mRNA was the splice product of a second 4.7-kb germ line transcript that initiated 50 base pairs upstream of J kappa 1. The interaction of the two kappa germ line promoters with nuclear binding factors is also examined. The potential role of these germ line transcripts in establishing the rearrangement potential of the locus is discussed.